Chitosan capped nanoscale Fe-MIL-88B-NH2 metal-organic framework as drug carrier material for the pH responsive delivery of doxorubicin. (14th August 2017) - Sivakumar, P; Priyatharshni, S; Nagashanmugam, K B; Thanigaivelan, A; Kumar, K
Abstract: In recent years nanoscale metal-organic frameworks (NMOFs) are contributing as an effective material for use in drug delivery and imaging applications due to their porous surfaces and easy surface modifications. In this work, Fe-MIL-88B-NH2 NMOFs were successfully synthesized on facile hydrothermal route and 2-aminoterephthalic acid (NH2 -BDC) was employed as a bridging ligand to activate amine functional groups on the surface. Amine functional groups not only serve as a structure stabilizing agent but also enhance the loading efficiency of the doxorubicin (DOX) anticancer drug. A pH responsive DOX release was realized by introducing a positively charged chitosan (Chi) capping layer. Upon Chi-coating, cleavage was observed in the Fe-MIL-88B-NH2 structure at acidic pH, while gel-like insoluble structure was formed at basic pH. By utilizing this phenomenon, a pH responsive DOX release system was developed by using Chi capped Fe-MIL-88B-NH2 NMOFs under the designed pH (4.0–8.0). The results suggest the Chi capped Fe-MIL-88B-NH2 can be a promising candidate for future pH responsive drug delivery systems.